PENERAPAN METODE MIND MAPPING BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Rahmi Gusliana; Yusnira; Nurhaswinda; Nurmalina; Masrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is the low creative thinking ability of class III students. This research aims to improve the creative thinking abilities of class III Salafiyah Ula Ibnu Jarir Bangkinang students. This research is classroom action research carried out in two cycles, each cycle consisting of two meetings. The subjects in this research were 1 teacher and 18 students, while the object of this research was a mind mapping method based on local wisdom to improve elementary school students' creative thinking abilities. The data collection techniques used in this research are observation, tests and documentation. Based on the results of research carried out in 2 cycles, the percentage results obtained in cycle I meeting 1 were 28%, cycle I meeting 2 was 33%, and in cycle II meeting 1 was 44%, cycle II meeting 2 was 72%. Based on the research results, it can be concluded that the mind mapping method based on local wisdom can improve the creative thinking abilities of class III Salafiyah Ula Ibnu Jarir Bangkinang students.